(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Transportation plays an important role in the development of a nation. It is regarded as a tool for the economic development of a nation. The peace and stability of the globe depend on the ease of social interaction and trade across nations. The issue of food insecurity affects the stability of a nation. Thus, this study examines the role of transportation systems in food security and stability in Osun State, Nigeria. This study adopts a survey research design in which secondary and primary data are both utilised. The result shows that the correlation coefficient (r) is 0.927 and the coefficient of multiple determinant (r2) is 0.893. It simply means that above 86% of the variation in independent variables may be attributed to a magnitude increase in the dependent variables, which are factors influencing the mobility of food items. Also, the F ratio, which is 146.193, was statistically significant at p value = 0.00. These factors are poor and inaccessible roads, accidents, theft, breakdown of vehicles, banditry, and harassment of traders. The study concluded that transportation systems play a crucial role in enhancing the mobility of food items to various markets. It was recommended that all roads should be greatly improved to enhance accessibility. More security personnel should be deployed on Nigerian roads to discourage food theft and banditry. Also, numerous levies against food traders should be reduced so that the prices of food items (groceries) can be affordable.